Evaluation of the degree of taper and convergence angle of full ceramo-metal crown preparations by different specialists centers at Assir Region, Saudi Arabia - Mohammed M Al-Moaleem; Mansoor Shariff; Amit Porwal; Essa A AlMakhloti; Shreyas Tikare (Saudi Journal of Medicine and Medical Sciences, 2015)
Background: Ceramo-metal crowns are commonly indicated for restoration of extensively damaged posterior teeth. Prosthodontists have ability to prepare teeth for retention, resistance, and longevity of the restorations. Objectives: The aim was to measure the degrees of the taper and convergence angle (CA) of dies prepared by different prosthodontists at Assir region, and the effect of the tooth position on the taper and CAs degrees. Materials and Methods: Eighty stone dies were obtained from specialist dental clinics, College of Dentistry at King Khalid University (KKU), Muhayil, Kamis-Mushayat and Assir Dental Centers. All the dies were mounted with the occlusal plane of the prepared teeth parallel to the floor. Photographs of buccal and proximal aspects were taken for each die. The photographs were transferred into a personal computer, AutoCAD software program was used to measure the mesio-distal (MD) and bucco-lingual (BL) taper and CA of each preparation. Analysis of variance (ANOVA) was used to test the level of significance difference, which was set at 5%. Results: The highest values were observed with Kamis-Mushayat Center for BL (31.89) taper and Assir Center for MD (38.21) and overall CA degrees (34.38). The mean values for KKU specialist dental clinics were the lowest for all parameters of CA degrees (22.91). ANOVA showed statistically significant (P < 0.05) differences with the mean CAs between all the four dental centers. The MD, BL taper and overall CA for all the premolar teeth was significantly lower than molar teeth. No statistical difference in the overall CA between maxillary and the mandibular arch (P > 0.05). Conclusions: The values of MD, BL taper and CA degrees carried-out by specialist at College of Dentistry, KKU are the lowest values of the prepared teeth compared with other dental centers at Assir region. There was no significant difference between maxillary and mandibular arch, while taper and CA are lower at premolars comparing to molars. The recommended taper and CAs are difficult to be achieved clinically.